ANALISA PENGIRIMAN OPTIMAL DENGAN METODE ECONOMIC ORDER QUANTITY(EOQ) KONDISI BACKORDER SME KEMPLANG BADAK PANGGANG - Agatha, Arselia; Sunarni, Theresia (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2020)
SME Kemplang Badak Panggang is an SME that sells Palembang-style Kemplang, which is baked and in the process requires sunlight to make dried kempang. Often during the manufacturing process to fulfill customer orders, this SME cannot complete the orders so it needs to be backordered. Because this the permanent customers, they are willing to wait. This research focuses on calculating the total annual production costs needed by considering backorder costs. The data needed is demand data for 2017-2018 in Jambi and Baturaja. By looking pattern of graph, it can be concluded that seasonal pattern, and forecasting are used for Hot Winter and Decomposition. Forecasting result are selected with the smallest MAD value. Data processing will begin by calculating the optimum quantity of backorder, the length of the waiting time and total costs for Jambi and Baturaja. Expected this research can help owner to find optimum costs during a year.